2010
DOI: 10.1002/ana.22128
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐JC virus antibodies: Implications for PML Risk Stratification

Abstract: This 2-step assay provides a means to classify MS patients as having detectable or not detectable levels of anti-JCV antibodies. The finding that all 17 of the pre-PML samples that were available tested seropositive, and none tested seronegative, warrants further research on the clinical utility of the anti-JCV antibody assay as a potential tool for stratifying MS patients for higher or lower risk of developing PML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
366
4
12

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 417 publications
(405 citation statements)
references
References 32 publications
23
366
4
12
Order By: Relevance
“…In the aforementioned study, one patient tested positive for the antibodies 2 months before PML diagnosis. This patient had tested negative for anti-JCV antibodies 15 months prior to PML diagnosis [67], indicating either exposure to JCV at some point between the two tests or that seroconversion is possible even in individuals who are anti-JCV antibody negative; it is estimated that patients seroconvert at a rate of 1%-2% per annum, prompting some clinicians to recommend biannual JCV antibody testing in anti-JCV antibodynegative patients [74]. Furthermore, a recent study of 200 patients with MS found that approximately 5% of those with undetectable anti-JCV antibodies in serum had high anti-JCV antibody values in cerebrospinal fluid, showing that levels of these antibodies in the two locations do not always correlate [75].…”
Section: Natalizumabmentioning
confidence: 99%
“…In the aforementioned study, one patient tested positive for the antibodies 2 months before PML diagnosis. This patient had tested negative for anti-JCV antibodies 15 months prior to PML diagnosis [67], indicating either exposure to JCV at some point between the two tests or that seroconversion is possible even in individuals who are anti-JCV antibody negative; it is estimated that patients seroconvert at a rate of 1%-2% per annum, prompting some clinicians to recommend biannual JCV antibody testing in anti-JCV antibodynegative patients [74]. Furthermore, a recent study of 200 patients with MS found that approximately 5% of those with undetectable anti-JCV antibodies in serum had high anti-JCV antibody values in cerebrospinal fluid, showing that levels of these antibodies in the two locations do not always correlate [75].…”
Section: Natalizumabmentioning
confidence: 99%
“…The overall JCV-positivity rates with this assay have ranged from approximately 50% to 60%. [20][21][22][23] Since this index was introduced, we no longer simply consider a patient's JCV serostatus, but also take into account the magnitude of positivity. Subjects with higher anti-JCV antibody indices are at higher risk of PML than JCV-positive patients with lower indices.…”
Section: Recommendations For Pml Risk Stratification Incorporating Thmentioning
confidence: 99%
“…24 Note that there is a false-negative rate of approximately 2.0% to 2.5% per year, and seroconversion occurs in approximately 2% to 8% of natalizumab-treated patients per year. 20,21 It is also important to note that there can be fluctuation in the JCV index at lower levels. Table 2 shows the panel's recommendations for natalizumab therapy depending on these three risk factors.…”
Section: Recommendations For Pml Risk Stratification Incorporating Thmentioning
confidence: 99%
“…However, at present, there is no blood biomarker of JCV activity that can be used alone to diagnose PML, and a failure to detect JCV DNA in the cerebrospinal fluid (CSF) does not rule out the possibility of having PML, particularly in the earlier stages of the disease (Brew et al, 2010;Cordioli et al, 2014). The only humoral parameter obtained routinely is the JCV seropositivity status, which is evaluated by detecting antibodies directed against JCV VP1 (the main surface JCV protein) using the single validated STRATIFY JC virus™ assay (Gorelik et al, 2010;Bozic et al, 2011;Lee et al, 2013).This assay allows neurologists to detect patients at higher risk of developing PML. In particular, three factors-the presence of anti-JCV antibodies, with a lower risk of developing PML in patients with low antibody titers , previous use of immunosuppressants, and protracted duration of treatment, especially if longer than 2 years-seem to contribute to the overall risk of natalizumab-associated PML .…”
Section: Known Predictive Markers For Natalizumab-related Pmlmentioning
confidence: 99%